(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The purpose of the study was to study the occurrence of hepatitis B virus genotypes in patients with hepatitis B+D in the Samarkand region. Materials and methods: The study included 40 patients with chronic viral hepatitis B+D. We determined general clinical laboratory blood tests, the viral load of HBV DNA? VDV RNA, genotypes of liver fibrosis by elastometry. Results: Viral load up to 2.000 IU/ml was detected in 32,5%, from 2000 to 20000 IU/ml in 30%, above 20,000 in %. With fibroscaning fibrosis data F0-F37,5%, F2-F3-15 %, F4-50%.